Induce mutations for Bavistin resistance in Trichoderma harzianum by UV-irradation - Al-araji, Alaa; Al-jboury, Mona; Aboud, Hadi (Iraqi Journal of Science, 2024)
The present study was conducted to induce mutations by UV- light in Trichoderma harzianum for tolerance of Bavistin fungicides which are commonly used to control soil born phytopathogens. The mycelium growth of T. harzianum T1, T2 was inhibited completely by 30 μg (a.i.) /ml PDA of Bavistin. Two isolates of Trichoderma harzianum T1 and T2 conidia suspensions 104 conidia / ml were irradiated by UV lights at 254, 320, 365nm wavelength for 10, 20, 40, 80, 160 min using UV dark room cabinet and spectrophotometer and cultured on PDA media containing 50, 60, 75, 100, and 150 μg (a.i) / ml Bavistin. A thirty one unstable mutants tolerant to Bavistin were obtained after irradiation the T. harzianum T1, T2 conidia suspension 104 conidia / ml by using UV dark room cabinet. While about 76975 Bavistin tolerant mutants were obtained by using UV spectrophotometer. Only twelve were stable and named (TAm1, TAm2, TAm3, TAa1, TAa2, TAa3, TAa4, TAa5, TAa6, TAa7, TAa9 and TAa11). Results daily radial growth and sporulation rate of stable mutants on fungicide culture media (Bavistin) revealed that the stable mutant TAa2 and TAa1 achevied the maximum average of (daily radial growth rate and sporulation). The stable mutants TAa1, TAa2, TAa3, TAa4, TAa5 and TAa7 which tolerates 150 μg (a.i)/ml Bavistin increased their ability to tolerate Bavistin up to 200 μg(a.i)/ml by using adaption technique.